Georgian Collonial Policy And 1875-1876 Armed Rebellion In Svaneti - Tchanturidze, Emzar (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2017)
Abolishment of Kartl-Kakheti kingdom in 1801 and its incorporation with the Russian Empire was the precondition of their occcupation, which was the abuse of 1783 Georgievsky agreement. The article discusses the aggressive politics of tsarism held in Georgian after 1801 and converting the political units of our country into ordinary administrative units of the empire. The political disharmony of different regions of Georgian enabled tsarizm to deprive the terriroties of Georgia thoroughly. The article highlights the anti-Georgian character of Russian collonial character ( asigning Russian management unacceptable for Georgians, conducting the law cases in Russian, Russification of the schools, endeavor of inserting Russian alphabet it the peripheral regions of Georgia…) and the destructive results of this politics. Georgian people never gave up the resistance against the Russian oppression and responded it with different cases of rebellion which were destroyed with abrupt policy.One of the case was 1875-1876 armed rebellion in highlands of Svaneti. The article describes the reasons of the rebellion, its process and tragic end on the basis of the official documents, scientific researches and articles.